A multi-level test for social regulatory focus and team member creativity: Mediating role of self-leadership strategies. Issue 8 (6th November 2017) - Lin, Chen-Ju
Abstract : Purpose: In this study, self-leadership strategy serves as a self-regulatory mediating mechanism of individual differences in predicting individual creativity because it is related to actions intended to lead their own goal-directed activities. The purpose of this paper is to explore the boundary conditions of the effect of regulatory focus on employee self-leadership behaviors. Design/methodology/approach: Considering the contextual influence, cross-level moderating effect of empowering leadership on the relationship between the promotion (prevention) focus and self-leadership has been examined. The research data were collected from 441 employees of 65 work teams from three software companies located in Northern Taiwan. A time-lagged design by implementing three time surveys was applied to minimize potential problems of cross-sectional design. At Time 1, employees completed the measures of promotion focus, prevention focus, empowering leadership, and individual-level control variables. At Time 2, employees reported the extent of their self-leadership at work. In the final survey, team leaders assessed the individual employee creativity. Findings: This study concludes several findings. When self-leading behavior-focused strategies are considered as mediators, the indirect relationships that promotion focus and prevention focus had with individual creativity were confirmed. As an influential team-level indicator, empowering leadership could moderate the relatedness between employees promotion-focused strategies and behavior-focused strategies that positively influenced on individual creativity. Originality/value: In this study, responding to the call by De Stobbeleir et al. (2011) to examine how employees actively manage their creative performance, the author zoomed in on self-leadership strategies and how these strategies relate to actual creative performance.